ANALISA KEPUASAN PENUMPANG TERHADAP KEAMANAN DI TERMINAL KEBERANGKATAN DOMESTIK BANDAR UDARA INTERNASIONAL YOGYAKARTA - Deva Dharmaputra; Kukuh Tri Prasetyo; Setyo Hariadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The Indonesian aviation industry is growing very rapidly. The more you compete in the airline industry, the more choices you have when it comes to products and services. One of them is the birth of the concept of "low cost airline". Yogyakarta International Airport is an airport with relatively high service for the flow of passengers and goods. Passenger and freight traffic is increasing year by year and cannot be compared to means to ensure flight safety such as X-ray operations which are not yet fully operational.To ensure that passengers are satisfied with the service, therefore it is necessary to calculate the number of x-rays needed to avoid long queues during the check-in process. Data were collected from direct observation and surveys. The analysis method uses quantitative methods such as validation, reliability testing, deterministic testing, partial calculation testing with SPSS applications, and manual calculations. The results of this study aimed to know the standard capacity of X-ray available with the needs of the number of passengers during peak hours so that there is no buildup in the inspection area and measure the level of service provided by Avsec to passengers at Yokyakarta International Airport, and can know the level of satisfaction of passengers to the service at the Domestic Departure Terminal of Yogyakarta International Airport.